A school-based fluoride mouth rinsing programme in Sarawak: a 3-year field study - Chen, C.J.A.; Ling, K.S.; Esa, R.; Chia, J.C.; Eddy, A.; Yaw, S.L. (2010)
Background: This study was undertaken to assess the impact of fluoride mouth rinsing on caries experience in a cohort of schoolchildren 3 years after implementation. Methods: 270 children aged 8-9 years from four schools in Sarawak were selected at baseline. Baseline data was collected to ensure that the selected schools did not differ significantly. Children from two schools rinsed with 0.2 sodium fluoride under supervision, while those from the other schools did not. Results: After 3 years, 242 schoolchildren remained in the study. At the end of the study, the mean DMFT for the test group was 2.3 (95 CI, 1.93-2.67) while the mean DMFT for the control group was 4.01 (95 CI, 3.39-4.63). The mean DMFS for the test group was 3.40 (95 CI, 2.68-4.12) while the mean DMFS for the control group was 6.67 (95 CI, 5.47-7.87). After 3 years, 24.2 of those in the test group remained caries free compared to 11.5 in the control group. The risk of developing caries decreased 0.52 times among the children from the 'test' group exposed to the fluoride mouth rinsing programme as compared to the unexposed 'control' group (RR = 0.48, 95 CI, 0.26-0.85). Discussion and conclusion: The findings show that a school-based weekly 0.2 sodium fluoride mouth rinsing programme is an effective caries preventive measure and should be implemented in fluoride-deficient areas as a means of reducing the prevalence of dental caries in these communities.